Bioinspired low-noise wing design for a two-winged flapping-wing micro air vehicle - Lu, Zhenbo; Debiasi, Marco; Nguyen, Quoc Viet; Chan, Woei L. (AIAA, 2018)
This work investigates the acoustic and thrust performances of different wing designs for a two-winged flapping-wing micro air vehicle (FW-MAV). The reference wings, made of a Mylar film membrane supported by carbon-fiber rods, produce a perceived overall noise of about 68.8 dBA when operating at the flapping frequency of 10 Hz typically required for flying such a flapping wing vehicle. This noise is much higher than the value of the environmental background. Wings of various materials and structural configurations are designed and tested in order to reduce the flapping-wing noise. Sound and force measurements are used to assess their acoustic and lift capabilities. It is found that a wing made with a highly elastic dielectric elastomer membrane can reduce the overall perceived noise of the flapping wing by 12 dBA while slightly increasing the thrust. The mechanisms leading to this noise reduction and their potential applications in quiet FW-MAVs are discussed.